A scoping review of mental health literacy in performing and creative artists: identifying current gaps and future directions - Li, Shelly-Anne; Sakata, Naoko; Donn, Gemma (Frontiers in Psychology, 2025)
IntroductionMental health literacy is a multifaceted construct that consists of helping individuals recognize the early warning signs of mental health conditions, understanding the concept of stigma and misconceptions associated with mental illness, encouraging appropriate help-seeking behaviors, and facilitating access to mental health services. However, mental health literacy remains a largely unexplored topic in artists’ health literature. This scoping review examines the conceptualization, operationalization, and measurement of mental health literacy in performing and creative artists.MethodsWe conducted a comprehensive search across multiple databases, including MEDLINE, CINAHL, PubMed, EMBASE, PsycINFO, Web of Science, and Cochrane. Our search was designed to identify articles relevant to mental health literacy among artists, encompassing aspects related to the understanding, identification, and education of mental health conditions. Two independent reviewers conducted both abstract and full-text screenings. Our findings are synthesized using the four components of mental health literacy as a framework for organization.ResultsOf the 669 unique citations, 26 articles met the inclusion criteria; of these, 23 focused on performing artists. The articles were published between 1997 and 2024, with at least 4,710 participants from nine countries. Only one study included a definition of mental health literacy. Sixteen articles included one of the four components of mental health literacy, nine included two, four included three, and one had all four components.DiscussionDespite the high prevalence of mental health challenges among performing and creative artists, there is a disproportionately low number of interventions aimed at increasing mental health literacy compared to other fields, such as sports medicine and education. This highlights the need for more comprehensive efforts to increase awareness and understanding of mental health issues among artists. Furthermore, the lack of consensus on the conceptualization, operationalization, and measurement of mental health literacy in this field prompts further research. A standardized definition and validated instrument could facilitate more robust research on mental health literacy in the artists’ health literature and help identify effective interventions. Future research can build on this review to develop and evaluate interventions aiming to improve mental health literacy in artists.